Optimizing Quality of Life Through an Adaptive Biophilic Architecture Sensory Approach - Gaizka Royhan Astawa; Andarita Rolalisasi; Febby Rahmatullah Masruchin (Kirana Publisher (KNPub), 2026)
Massive urbanization has created the phenomenon of